From Social Sharing to Security Lessons: Behaviors, Disclosure, and Cyber Threats (Journal of The Colloquium for Information Systems Security Education, 2026)
As social networking sites (SNSs) have become integral to daily life, concerns about privacy and cybersecurity risks have intensified. Malicious actors exploit SNSs for phishing, malware distribution, and identity-driven attacks, often leveraging personal information voluntarily disclosed by users. This study investigates the relationships between SNS usage, personal information disclosure, cybersecurity behaviors, and experiences with cybersecurity threats. We employed a mixed-methods approach, combining survey data from 275 participants with semi-structured interviews. Correlation analyses revealed that frequency of SNS use and usage motivations---particularly for meeting new people and for self-presentation---were positively associated with higher levels of personal information disclosure. Disclosure of personal information and frequency of SNS usage were also significantly correlated with reported experiences of cybersecurity threats, though less so with protective cybersecurity behaviors. Interview responses highlighted both direct encounters with threats and broader perceptions of privacy vulnerabilities. Together, these findings underscore the complex interplay between social behavior on SNSs and cybersecurity risks, suggesting that greater user education and platform-level safeguards are necessary to mitigate emerging threats. We conclude with implications for cybersecurity awareness efforts and recommendations for future research.
Keywords: social networking sites; cybersecurity behavior; personal information disclosure; social engineering; privacy; mixed methods